A Quantitative Well-to-Wheel Analysis of the Effect of Electric Vehicle Adoption on CO₂ Emissions in Indonesian Urban Logistics - Miftahol Arifin; Dinda Natasya Artaviana (International Forum of Researchers and Lecturers, 2025)
Urban logistics is a significant source of carbon emissions in Indonesia, and effective decarbonization strategies are required. EVs offer a promising solution, but their impact requires quantitative evaluation within the local context. This study analyzes the effect of adopting an electric van fleet on total well-to-wheel carbon emissions within an urban distribution network in Indonesia. This study employs a comparative case study method. A baseline scenario consisting of 25 diesel vans is compared to an intervention scenario where electric vans replace the entire fleet. The emission analysis was conducted using the WtW framework, utilizing specific emission factors for diesel fuel from the IPCC (2006) and the Java-Madura-Bali (JAMALI) grid emission factor from IESR (2023) to ensure contextual relevance. The transition to an electric fleet successfully reduces the total well-to-wheel carbon footprint by 13.63%. This reduction is equivalent to an absolute CO2 emission decrease of nearly 3 tons of CO₂ per month. Nevertheless, indirect emissions from electricity generation still contribute a significant carbon footprint, indicating that the national energy mix is highly dependent on the environmental benefits of EVs. This study concludes that fleet electrification is a viable and effective decarbonization strategy for Indonesia’s logistics sector, even with the current state of the electricity grid. However, fleet decarbonization efforts must run in parallel with policies for a national transition toward renewable energy to maximize the emission reduction potential of electric mobility. Future research should include the total cost of ownership (TCO) and life cycle assessment (LCA) for a more holistic evaluation.